Instytucja tzw. zgody następczej po nowelizacji z 11 marca 2016 r. w świetle standardów konstytucyjnych i konwencyjnych: [The institution of the so-called ex post facto consent after the amendment of 11 March 2016 in the light of constitutional and conventional standards] (Studia Prawnicze / The Legal Studies, 2017)
Artykuł 168b k.p.k. został wprowadzony do systemu prawa z mocy art. 1 pkt 35 ustawy z dnia 11 marca 2016 r. o zmianie ustawy – Kodeks postępowania karnego oraz niektórych innych ustaw i wszedł w życie z dniem 15 kwietnia 2016 r. (art. 28 ustawy nowelizującej). Tą samą ustawą nadano aktualne brzmienie art. 237a k.p.k. (art. 1 pkt 43 ustawy nowelizującej), które również weszło w życie z dniem 15 kwietnia 2016 r. (art. 28 ustawy nowelizującej). Oba wskazane przepisy normują instytucję tzw. zgody następczej. Przy czym art. 168b k.p.k. czyni to w odniesieniu do kontroli operacyjnej, a więc czynności pozaprocesowej, a art. 237a k.p.k. w odniesieniu do procesowej kontroli i utrwalania treści rozmów telefonicznych. The Act of 11 March 2016 amending the Code of Criminal Procedure and some other acts (Official Journal of Laws, item 437 as amended) introduced to the system of law Article 168b of the Code of Criminal Procedure and changed Article 237a of the Code of Criminal Procedure. These rules regulate the institution of the so-called ex post facto consent. The following paper analyzes Article 168b and Article 237a of the Code of Criminal Procedure in the light of standards stemming from the Constitution of the Republic of Poland and the Convention for the Protection of Human Rights and Fundamental Freedoms. This analysis first of all revealed that there are serious doubts as to the compatibility of Article 168b and Article 237a of the Code of Criminal Procedure with Article 47, Article 49, Article 51 (2) in conjunction with Article 31 (3) of the Constitution of the Republic of Poland.